2008
DOI: 10.1200/jco.2008.18.6288
|View full text |Cite
|
Sign up to set email alerts
|

Postresection CA 19-9 Predicts Overall Survival in Patients With Pancreatic Cancer Treated With Adjuvant Chemoradiation: A Prospective Validation by RTOG 9704

Abstract: Purpose CA 19-9 is an important tumor marker in patients with pancreatic adenocarcinoma. A secondary end point of Radiation Therapy Oncology Group trial 9704 was prospective evaluation of the ability of postresectional CA 19-9 to predict survival. Methods CA 19-9 expression was analyzed as a dichotomized variable (< 180 v ≥ 180) or (≤ 90 v > 90). Cox proportional hazards models were utilized to identify the impact of CA 19-9 expression on overall survival (OS). Actuarial estimates for OS were calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
197
4
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(216 citation statements)
references
References 17 publications
10
197
4
5
Order By: Relevance
“…In our study, median time from the end of concurrent CRT to post CRT CA 19-9 was 36 days (range, 0.00-168.81 days). In RTOG 9704, the median time from surgery to the blood draw for postoperative CA 19-9 determination was 45 days (range, 11 to 57 days) as a secondary end point of its phase III study (4). To correct for the variability in the time between CRT and evaluation of the first post CRT CA19-9 value, we chose to measure survival as a time-varying covariate from the time of post CRT CA19-9 measurement rather than from CRT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, median time from the end of concurrent CRT to post CRT CA 19-9 was 36 days (range, 0.00-168.81 days). In RTOG 9704, the median time from surgery to the blood draw for postoperative CA 19-9 determination was 45 days (range, 11 to 57 days) as a secondary end point of its phase III study (4). To correct for the variability in the time between CRT and evaluation of the first post CRT CA19-9 value, we chose to measure survival as a time-varying covariate from the time of post CRT CA19-9 measurement rather than from CRT.…”
Section: Discussionmentioning
confidence: 99%
“…Low postoperative serum CA 19-9 levels and a decrease in serial levels following surgery have been shown to correlate with survival (3). RTOG 9704 demonstrated a prognostic role for postoperative CA 19-9 levels in patients with resectable pancreatic carcinoma following surgery (4). The National Comprehensive Cancer Network recommends measurement of serum CA 19-9 level following surgery prior to the administration of adjuvant therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been extensively used as a pancreatic cancer biomarker at various phases of pancreatic cancer management (6,8,9,(11)(12)(13). The recommended upper limit for normal serum CA19-9 expression is 37 U/ml, as determined by the standard deviation of CA19-9 expression in the normal population (11,12,14). Several studies have demonstrated that early-and advanced-stage pancreatic cancer patients with normal serum CA19-9 expression (≤37 U/ml) had a significant survival advantage compared with patients with elevated serum CA19-9 expression (>37 U/ml) (11,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…The recommended upper limit for normal serum CA19-9 expression is 37 U/ml, as determined by the standard deviation of CA19-9 expression in the normal population (11,12,14). Several studies have demonstrated that early-and advanced-stage pancreatic cancer patients with normal serum CA19-9 expression (≤37 U/ml) had a significant survival advantage compared with patients with elevated serum CA19-9 expression (>37 U/ml) (11,14,15). However, the clinical features of pancreatic cancer occurring with normal CA19-9 levels remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 83 % of patients in CONKO-001 and 65 % of patients in ESPAC-3 had R0 resections, compared to 40 % in RTOG 97-04. Additionally, CONKO-001 excluded patients with postresection CA 19-9 levels greater than 2.5 times the upper limit of normal (90 U/ml), which was shown in separate analyses including RTOG 97-04 [30,31]. A report comparing patients from RTOG 97-04 with pancreatic head tumors, radiotherapy delivered per protocol, and CA 19-9 levels <90 U/ml compares favorably with CONKO-001 (median survival 24 vs. 22.1 months, 5-year overall survival 34 % vs. 21 %), even in the setting of only half the rate of R0 resection in CONKO-001 compared with RTOG 97-04, arguing that high-quality radiation may provide benefit.…”
Section: The Era Of Modern Radiotherapymentioning
confidence: 99%